Mother Behavior to Their Daughters As Seen in ''Pride and Prejudice" and "Little Women" - Fitri Arniati; Muhammad Darwis; Nurhayati Rahman; Fathu Rahman (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This research is to study about the mother behavior to their daughters as seen in "Pride and Prejudice" and "Little Women". The mother behavior to their daughters show the different way of women as a mother in bringing up their children according to their social and condition at the time. The data were taken from two novels entitled "pride and prejudice" and "little women" is the topic of the study. The  women held in the early 19th century and the late 19th century was described as one that belonged in the home as a wife and mother, and that should marry a man who can support their family. Also throughout the novel women's role in society was described as one that is to be accomplished in household  chore and those of entertainment, such as singing  and playing music. The role of women in society was a major theme throughout the novel "Pride and Prejudice" and "Little Women" The method used in this research  is a study of comparative literature to analyze mother behavior especially for Mrs. Bennet, Lady Catherine de Bourgh, These women have similarities and different behavior in find the right mate for their daughters. This study shows that every woman has characteristics in caring for their children and paying attention to the survival of their children.